State-of-the-art and emerging trends in analytical approaches to pharmaceutical-product commercialization. (December 2022) - Blue, Laura E; Guan, Xiaoyan; Joubert, Marisa K; Kuhns, Scott T; Moore, Stephanie; Semin, David J; Wikström, Mats; Wypych, Jette; Goudar, Chetan T
Abstract : The biopharmaceutical landscape continues to evolve rapidly, and associated modality complexity and the need to improve molecular understanding require concomitant advances in analytical approaches used to characterize and release the product. The Product Quality Attribute Assessment (PQAA) and Quality Target Product Profile (QTPP) frameworks help catalog and translate molecular understanding to process and product-design targets, thereby enabling reliable manufacturing of high-quality product. The analytical target profile forms the basis of identifying best-fit analytical methods for attribute measurement and continues to be successfully used to develop robust analytical methods for detailed product characterization as well as release and stability testing. Despite maturity across multiple testing platforms, advances continue to be made, several with the potential to alter testing paradigms. There is an increasing role for mass spectrometry beyond product characterization and into routine release testing as seen by the progress in multi-attribute methods and technologies, applications to aggregate measurement, the development of capillary zone electrophoresis (CZE) coupled with mass spectrometry (MS) and capillary isoelectric focusing (CIEF) with MS for measurement of glycans and charged species, respectively, and increased application to host cell protein measurement. Multitarget engaging multispecific modalities will drive advances in bioassay platforms and recent advances both in 1- and 2-D NMR approaches could make it the method of choice for characterizing higher-order structures. Additionally, rigorous understanding of raw material and container attributes is necessary to complement product understanding, and these collectively can enable robust supply of high-quality product to patients. Graphical Abstract: ga1 Highlights: Product Quality Attribute Assessment (PQAA) is foundational for product design. Quality Target Product Profile (QTPP) helps define the integrated control strategy. Analytical target profile (ATP) influences technology choice for measurement. Numerous emerging technologies for assessing biotherapeutics and small molecules.